2015
DOI: 10.1158/1078-0432.ccr-14-2751
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of [68Ga]-DOTATATE PET/CT to Other Functional Imaging Modalities in the Localization of SDHB-Associated Metastatic Pheochromocytoma and Paraganglioma

Abstract: Purpose Patients with succinate dehydrogenase subunit B (SDHB) mutation-related pheochromocytoma/paraganglioma (PHEO/PGL) are at a higher risk for metastatic disease than other hereditary PHEOs/PGLs. Current therapeutic approaches are limited but the best outcomes are based on the early and proper detection of as many lesions as possible. Because PHEOs/PGLs overexpress somatostatin receptor 2 (SSTR2), the goal of our study was to assess the clinical utility of [68Ga]-DOTA(0)-Tyr(3)-octreotate ([68Ga]-DOTATATE)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
187
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 243 publications
(206 citation statements)
references
References 38 publications
5
187
1
5
Order By: Relevance
“…All CT and MRI scans of the neck, chest, abdomen, and pelvis were obtained as follows and previously described (13). CT scans of the neck, chest, abdomen, and pelvis were obtained using the following devices: Somatom Definition AS and Somatom Definition Flash (Siemens Medical Solutions) and Aquilion ONE (Toshiba Medical Systems).…”
Section: Imaging Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…All CT and MRI scans of the neck, chest, abdomen, and pelvis were obtained as follows and previously described (13). CT scans of the neck, chest, abdomen, and pelvis were obtained using the following devices: Somatom Definition AS and Somatom Definition Flash (Siemens Medical Solutions) and Aquilion ONE (Toshiba Medical Systems).…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…As previously described and supported (13,14), a positive result on at least 2 different functional imaging modalities, or at least 1 functional imaging study and confirmation on CT/MRI, was counted as true disease. Furthermore, histologic proof was available for 18 lesions.…”
Section: Analysis Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…17 A recent study has also demonstrated the superiority of 68 Ga-DOTATATE PET/CT in SDHBrelated metastasis over the previously mentioned functional imaging methods. 18 The 18 F-FDG PET/CT can differentiate SDHx-related HNPGL from sporadic ones with 80% accuracy. 19 However, no such data are available in children.…”
Section: Choice Of Nuclear Imagingmentioning
confidence: 99%
“…In adults, it has been shown that 18 F-fluro-deoxy-glucose (FDG) positron emission tomography/computerized tomography (PET/CT) and 18 F-fluro-dopamine PET are more sensitive in detecting metastasis in SDHB mutation carriers, whereas 18 F-fluro-dihydroxyphenylalanine PET/CT is more useful to detect non SDHB metastasis. 17 A recent study has also demonstrated the superiority of 68 Ga-DOTATATE PET/CT in SDHBrelated metastasis over the previously mentioned functional imaging methods.…”
Section: Choice Of Nuclear Imagingmentioning
confidence: 99%